The Role of Visionary Leadership in Developing Competitive Islamic Education Systems - Nur Efendi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This study investigates the role of visionary leadership in developing a competitive Islamic education system at a junior secondary school in Tulungagung. The study focuses on how leadership shapes institutional direction, influences educational competitiveness, and connects leadership practices with performance outcomes. A qualitative case study design was applied to explore leadership practices, teacher experiences, and institutional processes within their natural context. Data were collected through semi-structured interviews, observations of school activities, and document analysis, followed by thematic analysis. The findings reveal that visionary leadership provides a clear institutional direction that integrates academic excellence with Islamic values and guides instructional and organizational practices. Leadership actions such as strategic planning, supervision, and professional support contribute to improved teaching quality, student engagement, and institutional reputation. The study also identifies a dynamic interaction in which leadership vision shapes practices, educational processes support competitiveness, and performance outcomes provide feedback for leadership refinement. These results indicate that visionary leadership plays a central role in sustaining continuous improvement and strengthening the competitiveness of Islamic education systems.